Optimization Design of Hybrid Mufflers on Broadband Frequencies Using the Genetic Algorithm - CHIU, Min-Chie (Archives of Acoustics, 2011)
Recently, there has been research on high frequency dissipative mufflers. How-ever, research on shape optimization of hybrid mufflers that reduce broadband noisewithin a constrained space is sparse. In this paper, a hybrid muffler composed ofa dissipative muffler and a reactive muffler within a constrained space is assessed.Using the eigenvalues and eigenfunctions, a coupling wave equation for the perfo-rated dissipative chamber is simplified into a four-pole matrix form. To efficientlyfind the optimal shape within a constrained space, a four-pole matrix system usedto evaluate the acoustical performance of the sound transmission loss (STL) is eval-uated using a genetic algorithm (GA).A numerical case for eliminating a broadband venting noise is also introduced. Toverify the reliability of a GA optimization, optimal noise abatements for two puretones (500 Hz and 800 Hz) are exemplified. Before the GA operation can be carriedout, the accuracy of the mathematical models has been checked using experimentaldata. Results indicate that the maximal STL is precisely located at the desired targettone. The optimal result of case studies for eliminating broadband noise also revealsthat the overall sound power level (SWL) of the hybrid muffler can be reducedfrom 138.9 dB(A) to 84.5 dB(A), which is superior to other mufflers (a one-chamberdissipative and a one-chamber reactive muffler). Consequently, a successful approachused for the optimal design of the hybrid mufflers within a constrained space hasbeen demonstrated.